The Future Orientation of Past Memory: The Role of BA 10 in Prospective and Retrospective Retrieval Modes - Underwood, Adam G.; Guynn, Melissa J.; Cohen, Anna-Lisa (Frontiers in Human Neuroscience, 2015)
Klein made the provocative suggestion that the purpose of human episodic memory is to enable individuals to plan and prepare for the future. In other words, although episodic (retrospective) memory is about the past, it is not actually for the past; it is for the future. Within this focus, a natural subject for investigation is prospective memory, or memory to do things in the future. An important theoretical construct in the fields of both retrospective memory and prospective memory is that of a retrieval mode, or a neurocognitive set or readiness to treat environmental stimuli as potential retrieval cues. This construct was originally introduced in a theory of episodic (retrospective) memory and has more recently been invoked in a theory of how some prospective memory tasks are accomplished. To our knowledge, this construct has not been explicitly compared between the two literatures, and thus this is the purpose of the present article. Although we address the behavioral evidence for each construct, our primary goal is to assess the extent to which each retrieval mode appears to rely on a common neural region. Our review highlights the fact that a particular area of prefrontal cortex (BA 10) appears to play an important role in both retrospective and prospective retrieval modes. We suggest, based on this evidence and these ideas, that prospective memory research could profit from more active exploration of the relevance of theoretical constructs from the retrospective memory literature.